Parathyroid Hormone versus Bisphosphonate Treatment on Bone Mineral Density in Osteoporosis Therapy: A Meta-Analysis of Randomized Controlled Trials - Shen, Longxiang (Public Library of Science, 2011)
BACKGROUND: Bisphosphonates and parathyroid hormone (PTH) represent the antiresorptive and anabolic classes of drugs for osteoporosis treatment. Bone mineral density (BMD) is an essential parameter for the evaluation of anti-osteoporotic drugs. The aim of this study was to evaluate the effects of PTH versus bisphosphonates on BMD for the treatment of osteoporosis. METHODS/PRINCIPAL FINDINGS: We performed a literature search to identify studies that investigated the effects of PTH versus bisphosphonates treatment on BMD. A total of 7 articles were included in this study, representing data on 944 subjects. The pooled data showed that the percent change of increased BMD in the spine is higher with PTH compared to bisphosphonates (WMD = 5.90, 95% CI: 3.69–8.10, p<0.01,). In the hip, high dose (40 µg) PTH (1–34) showed significantly higher increments of BMD compared to alendronate (femoral neck: WMD = 5.67, 95% CI: 3.47–7.87, p<0.01; total hip: WMD = 2.40, 95%CI: 0.49–4.31, p<0.05). PTH treatment has yielded significantly higher increments than bisphosphonates with a duration of over 12 months (femoral neck: WMD = 5.67, 95% CI: 3.47–7.86, p<0.01; total hip: WMD = 2.40, 95% CI: 0.49–4.31, P<0.05) and significantly lower increments at 12 months (femoral neck: WMD = −1.05, 95% CI: −2.26–0.16, p<0.01; total hip: WMD: −1.69, 95% CI: −3.05–0.34, p<0.05). In the distal radius, a reduction in BMD was significant between PTH and alendronate treatment. (WMD = −3.68, 95% CI: −5.57–1.79, p<0.01). DISCUSSION: Our results demonstrated that PTH significantly increased lumbar spine BMD as compared to treatment with bisphosphonates and PTH treatment induced duration- and dose-dependent increases in hip BMD as compared to bisphosphonates treatment. This study has also disclosed that for the distal radius, BMD was significantly lower from PTH treatment than alendronate treatment.